ANALISIS PREFERENSI KONSUMEN DALAM PEMBELIAN BERAS PREMIUM DI PASAR MODERN KOTA BATURAJA - Sahudin, Ervina Yuliyanti; Lastinawati, Endang; Septianita, Septianita (Universitas Galuh, 2023)
This research has directions to find out the stages of the consumer decision-making process in purchasing premium rice, and how consumer preferences relate to rice attributes in purchasing premium rice in the Modern Market of Baturaja City. This research was conducted by survey method. Samples were taken using the accidental sampling method of 60 consumers of premium rice in the Modern Market, Baturaja City. Data processing was carried out in a quantitative descriptive manner, using conjoint analysis. The results of this study indicate the stages of the purchasing decision process through the stages of need recognition, information search, evaluation of alternatives and purchasing decisions. Consumer preferences related to rice attributes in purchasing premium rice at the Modern Market in Baturaja City consider that the most important attributes are fluffiness, shape, size and color.